Position-Sensitive Silicon Detector for X-Ray Difractometry of Rapid Processes - Pugatch, V.M. (Science and Innovation, 2024)
The results of development and application of position sensitive microdetectors for studying dynamics of rapid processes in metals and alloys under heating/cooling by means of high-speed radiography have been presented.